Tingkat Depresi Pasien Lansia Gagal Ginjal Kronis Yang menjalani Hemodialisa Di Kota Semarang - Laura Khattrine Noviyanti; Ni Made Ayu Wulansari; Rindi Heryanti (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Chronic kidney failure is a condition that occurs due to a decrease in the ability of the kidneys to maintain balance in the body Depression is an emotional condition characterized by extreme sadness, feelings of guilt and worthlessness, withdrawal, and loss of interest in sleeping and having sex and other pleasurable things. The purpose of this study was to determine the describe the level of depression in patients with chronic kidney failure who underwent hemodialysis therapy in the hemodialysis room at the Renal and Hypertension Clinic in Semarang. This type of research uses a quantitative methodology with a quantitative descriptive design. The result showed that 54 respondents have 18 (33,3%) respondents did not experience depression, 33 (61.1%) experienced mild depression and 3 (5.6%) experienced moderate depression. The conclusion of this study was that most patients undergoing hemodialysis experienced depression with the highest level of depression being mild depression, this was caused by the length of time undergoing hemodialysis itself or other factors such as work, income, needs and family support